2006
DOI: 10.1016/s0210-4806(06)73516-1
|View full text |Cite
|
Sign up to set email alerts
|

Validez de las pruebas utilizadas en el diagnóstico inicial y su concordancia con el diagnóstico final en pacientes con sospecha de hiperplasia benigna de próstata

Abstract: Concordance between BPH initial diagnosis based on MH+I-PSS+DRE+PSA and diagnosis based on a full range of tests was high, thus allowing recommending the use of this group of initial diagnostic procedures, which are available to the primary care physician, not only as a first diagnostic step in patients with suspected BPH, but also as a valid strategy to prevent unnecessary delay in its initial management and to facilitate appropriate referral from primary to specialized care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Clinical study demonstrated that men with prostate volume ≥ 31 mL, PSA ≥ 1.6 ng/mL, or Q max⁡⁡ < 10.6 mL/sec at baseline had a significantly increased risk of overall clinical progression of BPH [29]. Although IPSS and PSA are simple BPH diagnostic factors used in the primary care setting, a previous study showed a high correlation between BPH diagnosed by simple tests (medical history, IPSS, digital rectal examination (DRE), and PSA) and that diagnosed by a full battery of tests including ultrasonographic assessment of residual and prostatic volume, and uroflowmetry [30]. Thus, these factors may also be useful as predictors of BPH progression.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical study demonstrated that men with prostate volume ≥ 31 mL, PSA ≥ 1.6 ng/mL, or Q max⁡⁡ < 10.6 mL/sec at baseline had a significantly increased risk of overall clinical progression of BPH [29]. Although IPSS and PSA are simple BPH diagnostic factors used in the primary care setting, a previous study showed a high correlation between BPH diagnosed by simple tests (medical history, IPSS, digital rectal examination (DRE), and PSA) and that diagnosed by a full battery of tests including ultrasonographic assessment of residual and prostatic volume, and uroflowmetry [30]. Thus, these factors may also be useful as predictors of BPH progression.…”
Section: Discussionmentioning
confidence: 99%